Nuclear AREG affects a low-proliferative phenotype and contributes to drug resistance of melanoma: molecular cancer biology - Seefried, Felix; Haller, Lucia; Fukuda, Shinji; Thongmao, Aranya; Schneider, Nadja; Utikal, Jochen; Higashiyama, Shigeki; Bosserhoff, Anja Katrin; Kuphal, Silke (International journal of cancer, 2022)
AMPHIREGULIN (AREG) is a multifaceted molecule, which acts not only as an extracellular ligand for EGF receptor (EGFR), but also as an intracellular signaling molecule. It remains elusive, however, whether AREG has a tumor suppressive or oncogenic role in melanoma. Here, we found that several melanoma cell lines express AREG, but the expression does not correlate with that of EGFR. Recombinant AREG and the neutralizing antibody experiments showed that intracellular AREG plays an important role in melanoma, implying a divergent function of AREG in addition to the role as a ligand for EGFR. Further investigation of this mechanism revealed that particularly nuclear-localized AREG regulates IGF-1R, P21 (Cip1/Waf1), TP53 and JARID1B protein accumulation in the nucleus. Furthermore, manipulation of nuclear AREG levels has influence on heterochromatin condensation (HP1beta, SETDB1) and trimethylation of histones H3K9 and H3K4. As these molecules correspond to previously identified markers for slow-cycling drug resistant cells, we speculate that nuclear AREG predisposes cells to resistance to therapy. According to the hypothesis, we detected the accumulation of AREG in the nucleus of SK-Mel-28-VR, which was cultured under Vemurafenib (VR) selection pressure, and this correlates with JARID1B expression. Here, knockdown of AREG makes the previously resistant cells more sensitive to VR treatment, resulting in inhibited proliferation. Taken together, we suggest that nuclear AREG affects a slow-cycling phenotype and increases resistance to VR, raising a possibility that AREG might be a potential therapeutic target for resistance in melanoma.
Erstmals online veröffentlicht: 22. August 2022
Gesehen am 02.09.2024